Prediction of disease relapses by multibiomarker disease activity and autoantibody status in patients with rheumatoid arthritis on tapering DMARD treatment. Issue 9 (19th October 2015) - Rech, Juergen; Hueber, Axel J; Finzel, Stephanie; Englbrecht, Matthias; Haschka, Judith; Manger, Bernhard; Kleyer, Arnd; Reiser, Michaela; Cobra, Jayme Fogagnolo; Figueiredo, Camille; Tony, Hans-Peter; Kleinert, Stefan; et al.
Abstract : Objective: To analyse the role of multibiomarker disease activity (MBDA) score in predicting disease relapses in patients with rheumatoid arthritis (RA) in sustained remission who tapered disease modifying antirheumatic drug (DMARD) therapy in RETRO, a prospective randomised controlled trial. Methods: MBDA scores (scale 1–100) were determined based on 12 inflammation markers in baseline serum samples from 94 patients of the RETRO study. MBDA scores were compared between patients relapsing or remaining in remission when tapering DMARDs. Demographic and disease-specific parameters were included in multivariate logistic regression analysis for defining predictors of relapse. Results: Moderate-to-high MBDA scores were found in 33% of patients with RA overall. Twice as many patients who relapsed (58%) had moderate/high MBDA compared with patients who remained in remission (21%). Baseline MBDA scores were significantly higher in patients with RA who were relapsing than those remaining in stable remission (N=94; p=0.0001) and those tapering/stopping (N=59; p=0.0001). Multivariate regression analysis identified MBDA scores as independent predictor for relapses in addition to anticitrullinated protein antibody (ACPA) status. Relapse rates were low (13%) in patients who were MBDA−/ACPA−, moderate in patients who were MBDA+/ACPA− (33.3%) and MBDA−ACPA+ (31.8%) and high in patients who were MBDA+/ACPA+ (76.4%). Conclusions: MBDA improved the prediction of relapses in patients with RA in stable remission undergoing DMARD tapering. If combined with ACPA testing, MBDA allowed prediction of relapse in more than 80% of the patients. Trial registration number: EudraCT 2009-015740-42.